Minority Shareholders Activism in Family Firms: A Comparative Study of Indonesian and South Korean Law - Widjaja, Jesslyn; Prisandani, Ulya Yasmine (Fakultas Hukum Universitas Hang Tuah, 2025)
Family firms significantly contribute to the economies of Indonesia and South Korea. Despite their importance, these firms face challenges related to succession and minority shareholder rights. Indonesia lacks a robust regulatory framework for minority shareholder activism, relying primarily on the Indonesian Company Law despite the existence of the General Guidelines for Governance of Indonesian Family-Owned Businesses. In contrast, South Korea's chaebols, large family-controlled conglomerates, face stricter regulatory oversight to protect minority shareholders, including the Monopoly Regulation and FairTrade Act and the Korean Stewardship Code. Therefore, this paper aims to find the differences between Indonesian and South Korean legal regime on the minority shareholder activism regulation for family firms, while also aiming to bring practical policy suggestions. To achieve such purpose, this study employs a juridical legal method with comparative approach. The study provides comparative analysis from the two different jurisdictions based on its regulations, and suggesting that providing stricter regulation on institutional investors for family-firms, as well as adding the guidelines with more specific recommendation for minority shareholding member of family firms may help in promoting a more equitable corporate governance regime in family-owned businesses.